Analysis of The Role of Organizational Culture in Optimizing Employee Performance in Islamic Banks - Bayu Indra Setia; Tjutju Yuniarsih; Hady Siti Hadijah; Atty Tri Juniarti (Jurnal Manajemen Bisnis, 2022)
Islamic banking in Indonesia is experiencing an upward trend, which has an impact on the increasing demand for Islamic products. The organizational culture of Islamic banks is based on a system based on the Qur'an and As-Sunnah in the company's activities. The research method used is descriptive qualitative, with 21 informants from various circles. The implementation of Islamic organizational culture in improving performance and carrying out activities based on the MASLAHAH cultural value in each employee becomes a guideline even though employee performance is still in the progress stage of achieving business plan targets.